Campanha (1890-1930) : a princesinha do sul quer ser moderna - Rômulo Nascimento Marcolino (2016)
This paper aims to investigate how the representations of the city of Campanha are configured, especially regarding its urbanization (or lack of it) in the period of the First Republic since our understanding that it was then that the dispute towards city projects began to accentuate. Urbanism in Campanha, such as in many Brazilian cities suffered great influence from speeches and actions of the sanitary medical field and the forces of engineering. The improvement work, basted to the development of new habits, arised as a possible solution to rebuild that which was one of the main villages of the Minas Gerais province until the first half of the 19th century. Through the creation of new norms for the law and the press, we perceive the effort of intellectuals, politicians, professors, engineers and doctors in inserting Campanha in the inexorable march for progress and civilization that all peoples would be submitted to. In chapter one, we analyzed the construction and sharing of the notion of decadence in the passage from Empire to Republic by the memories of Francisco de Paula Ferreira Rezende. In the following chapter, we sought to identify the effort in the incipient bureaucracy of the State in orienting the paths of modernization of Brazilian cities with the insertion of medical professionals and engineers, interweaving knowledge and power. The final chapter focused on the operations made in the body of the legendary Campanha pointing its specificities. We pointed out that the speeches of the elite of Campanha, through sanitation, embellishment of houses and squares, electricity, mail offices, banks, automobiles and photographs, forge the representation of a healthy, rejuvenated, modern and cult city, shaken by a new strength, that was able to find its new place of pride in the Minas Gerais south region and to attend the demands of capitalism in a process full of tensions.